Parental motivational beliefs, school involvement, and perceptions of adolescent academic self-efficacy - Puklek Levpušček, Melita (Revija za elementarno izobraževanje, 2026)
Grounded in the revised Hoover-Dempsey and Sandler model of parental involvement, this study examined motivational beliefs of parents regarding their school involvement, specific forms of involvement, and how these relate to parents’ perceptions of their child’s academic self-efficacy. Using a quantitative survey design, data were collected from a sample of 331 Slovenian parents of adolescents aged 12 to 15 years. Parents reported high levels of general invitation to participate in school, high levels of beliefs about their active role in their child’s education, and generally positive attitudes toward school. These motivating beliefs were consistently and positively associated only with their direct involvement at the school level. Both forms of involvement (school and home activities) were negatively related to adolescents’ academic self-efficacy.
Keywords: academic self-efficacy; adolescents; mladostniki; motivacijska prepričanja; motivational beliefs; parental involvement; parents; starševsko vključevanje; starši; učna samoučinkovitost